Kontra Publik Keagamaan dalam Media Baru: Islam, Kebudayaan Populer, dan Media Sosial pada Gerakan #IndonesiaTanpaJIL - Imam Ardhianto (Antropologi Indonesia, 2016)
This article explores the rise of contemporary Islamic movement that emerged as a result of a counter-public phenomenon over the discourse of liberal Islam in Indonesia. The phenomena explain the new entry point to understand the relationship between social media, popular culture, and the articulation of Islamic identity and piousness among urban youth in Indonesia. Taking case on the emerging popular-religious movement of #IndonesiatanpaJIL, that were arise from social media sites (Twitter, Facebook, and Youtube), this article examined how this movement was creatively playing Islamic discourse and the notions of nationalism/citizenship through urban pop culture materiality and commercialized public spaces. This appropriation had been influential to propagate their religious ideology and piety and by doing so showing their effective modality and mode of circulation.Keyword: Counter-Public, Islamic Identity, Social Media, Popular Culture, Public Sphere